Intergenerational co-residence during later life in Europe and China. (April 2019) - Emery, Tom; Dykstra, Pearl A.; Djundeva, Maja
Individuals in China are much more likely than Europeans to live with their adult children during later life. In this paper, we examine the extent to which this holds true across the diverse contexts and circumstances faced by Europeans and Chinese. We use comparative data from the Survey for Health, Ageing and Retirement in Europe and the China Family Panel Studies to examine cross-national differences in whom adults in later life choose to live with. We find that in rural China and among urban migrants there is a tendency to live with higher-educated children, whilst among urban Chinese and Europeans, individuals live with those with lower education levels. We also find that in Europe there is only a small preference for living with male adult children, whilst across China this preference is much stronger. However, we also note that this preference is weakest in urban China. These findings indicate strong differences in co-residence patterns between China and Europe, but also some similarities between specific subpopulations. We explain these differences and similarities using a social policy framework.